Influence of the IGFBP3-202A/C Gene Polymorphism on Clinical Features and Surgery Outcome in Acromegalic Patients - Gao, Ming; Zhu, Bin; Li, Ping; Zhang, Guojun; Chen, Kelin; Lv, Hong; Ma, Ruimin; Zhang, Limin; Fan, Yubo; Kang, Xixiong (Frontiers in Endocrinology, 2018)
Purpose: Excess growth hormone (GH) secretion in acromegaly patients results in increased levels of IGF-1 expression, which causes the clinical manifestations of acromegaly. IGF-1 levels are attenuated by IGFBP3, and a polymorphism in the promoter of IGFBP3 is known to affect the circulating level of IGFBP3 protein. The aim of the study was to evaluate the association of the IGFBP3 gene polymorphism with clinical features and surgery outcomes in acromegaly. We also investigate the difference in IGFBP3 polymorphism between acromegaly and general population. Methods: The study included 102 acromegalic patients and 142 sex- and age-matched healthy controls. The genotyping of IGFBP3 was carried out using the MassARRAY method. Patients were followed up for 4–12 months to estimate the neurosurgical effects. Clinical data were obtained from the medical records. Results: The CC genotype, which is associated with decreased IGFBP3 levels, was less common in acromegaly patients than among the healthy controls; although, this correlation was not significant (P = 0.056). There was no association of the IGFBP3 gene polymorphism with glucose, lipid, phosphorus, blood urea nitrogen, creatinine or uric acid levels. Additionally, there was no association between tumor size, texture, or hemorrhage/cyst, except there was a trend that more patients with the C allele (P = 0.054) needed additional treatment post-operation than did patients carrying the A allele (OR 1.985, 95% CI 0.983–4.008). Moreover, higher IGF-1 values after treatment were observed in patients carrying the C allele (P = 0.012 and P = 0.014 according to the additive model and dominant model, respectively). Conclusion: Polymorphisms in IGFBP3 may not influence metabolic parameters or pituitary tumor characteristics in acromegalic patients, but they may be associated with the hormone levels and surgery effects.